Experiment with the X-band radar at the Nizhny Novgorod cable car: First Results - Ponur Kirill Aleksandrovich; Titchenko Yuriy Andreevich; Karaev Vladimir; Meshkov Evgeniy Mihaylovich; Panfilova Mariya Andreevna; Krylov Andrey Vladimirovich; Lebedev I.; Khakin E. (Russian Journal of Earth Sciences, 2023)
The first results of data processing of the experiment on the Nizhny Novgorod cable car are presented. A pulsed X-band radar was installed on a technological trolley and performed measurements while moving in two modes that worked sequentially. In the radio altimeter mode, the reflected waveform was measured and the distance to the scattering surface was determined. In the Doppler mode, the Doppler spectrum of the reflected signal was measured, which contains information about the statistical parameters of the surface. Data processing was carried out and the first results confirmed the assumption that the Doppler spectrum can be an effective tool for classifying the type of the underlying surface according to the "ice/water" criterion. Subsequent data processing will allow us to evaluate the accuracy of the developed algorithms.